2021
DOI: 10.1097/md.0000000000025141
|View full text |Cite
|
Sign up to set email alerts
|

The effect of insulin pump combined with ulinastatin on the levels of PCT, TG, PTX-3, and CX3CL1 in patients with diabetic ketoacidosis and pancreatitis

Abstract: The aim of this research is to observe the effect of insulin pump combined with Ulinastatin on the levels of procalcitonin (PCT), triglycerides (TG), pentraxin-3(PTX-3), and C-X3-C motif chemokine ligand 1 (CX3CL1) in patients with diabetic ketoacidosis and pancreatitis. A total of 72 patients with diabetic ketoacidosis and pancreatitis who were admitted to our hospital from February 2016 to February 2020 were selected as the research subjects. They were divided into study groups (36 cases, given in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the present study, UTI intervention was used to reduce the incidence rate of total 30-day mortality and MODS. Wei [29] reported that an insulin pump combined with UTI can shorten the recovery time of clinical symptoms and reduce the levels of inflammatory factors after diabetic ketoacidosis complicated with pancreatitis. Xubijing combined with UTI can improve the outcome, decrease the inflammatory response, and promote the recovery of the patient’s immune function and liver function in traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, UTI intervention was used to reduce the incidence rate of total 30-day mortality and MODS. Wei [29] reported that an insulin pump combined with UTI can shorten the recovery time of clinical symptoms and reduce the levels of inflammatory factors after diabetic ketoacidosis complicated with pancreatitis. Xubijing combined with UTI can improve the outcome, decrease the inflammatory response, and promote the recovery of the patient’s immune function and liver function in traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions from these research reports should be treated with caution, however, because of their limited sample sizes or retrospective nature. Conversely, Wei et al [ 38 ] reported that after diabetic ketoacidosis complicated with AP, the recovery period of clinical symptoms and the levels of inflammatory mediators may be reduced by using an insulin pump in conjunction with UTI. Thus, the current investigation approved a large single-center RCT to verify the therapeutic benefits of UTI in severe AP.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation criteria of clinical efficacy were as follows [9,10] . Markedly effective: all clinical symptoms disappeared, fasting blood glucose <11.1 mmol/L, pH was 7.35 to 7.45, serum bicarbonate was 22 to 28 mmol/L, urine ketone body was negative, and blood ketone body <0.3 mmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation criteria of clinical efficacy were as follows. [9,10] Markedly effective: all clinical symptoms disappeared, fasting blood glucose <11.1 mmol/L, pH was 7.35 to 7.45, serum bicarbonate was 22 to 28 mmol/L, urine ketone body was negative, and blood ketone body <0.3 mmol/L. Effective: Partial clinical symptoms improved, fasting blood glucose <16.7 mmol/ L, pH was 7.35 to 7.45, serum bicarbonate was 22 to 28 mmol/L, urine ketone body was negative, and blood ketone body <0.3 mmol/L.…”
Section: Observation Indexesmentioning
confidence: 99%